Relationship between ecological parameters and environmental quality of three streams in the upper Paraná River basin - Ariane Aparecida Gouveia; Carlos Eduardo da Silva; Jéssica Aline Soares de Abreu; Fagner de Souza (Biotemas, 2013)
Aquatic environments frequently suffer great environmental disturbances, and alternative actions for biodiversity conservation must be taken to prevent the reduction of species richness in areas impacted. Given this, we started with the hypothesis that among natural and impacted streams, there are differences in the correlation between ecological parameters and environmental quality. The fish assemblages in three streams in the upper Paraná River basin were surveyed, and for each stream the ecological structures were related to environmental quality. Comparisons between the environmental integrity and ecological parameters were made. We collected 8,028 individuals, distributed in 3 orders, 6 families, 9 genera and 11 species. Low values in ecological indexes together with low habitat quality were found for one of the streams (Japira Stream). This is probably because there are a large number of residences in the surrounding area that are degrading the environmental complexity. These facts indicate that restoration measures, such as restructuring the riparian vegetation and offering environmental education programs, must be initiated to promote the recovery and environmental preservation of these areas.